The Penggunaan Sistem Pakar Dalam Mendiagnosis Penyakit Tanaman Padi Menggunakan Metode Fuzzy Logic - Ridwan Al Husyairi; Bayu Setiawan; Rafael Muhamad Gibran fahrezi; Muhamad Aldi Septian; Perani Rosyani (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2023)
This study describes the use of an expert system with the fuzzy logic method as a potential approach in diagnosing rice plant diseases. The aim is to improve the health and productivity of rice plants, as well as provide effective and efficient solutions for farmers. The basic concept of an expert system, the Fuzzy Logic method, and the implementation of an expert system in diagnosing diseases in rice plants are described in this study. Fuzzy methods are used to overcome complexity and ambiguity in the problem domain, model expert knowledge, and handle uncertain, incomplete, and ambiguous data. This expert system is expected to help rice farmers and related parties in identifying and treating diseases in rice plants, as well as increasing efficiency and service quality. The use of an expert system in diagnosing rice plant diseases with the Fuzzy Logic method can make a positive contribution in agriculture. This research is a valuable source of information for farmers, agricultural experts, and researchers interested in developing expert systems to support better growth and production of rice plants.